Anthropologies of Revolution Forging Time, People, and Worlds - Cherstich, Igor (University of California Press, 2020)
"What can anthropological thinking contribute to the study of revolutions? The first book-length anthropological approach to revolutions, Anthropologies of Revolution proposes that revolutions should be seen as concerted attempts to radically reconstitute the worlds people inhabit. Viewing revolutions as all-embracing, world-creating projects, the authors ask readers to move beyond the idea of revolutions as acts of violent political rupture, and instead regard them as processes of societal transformation that penetrate deeply into the fabric of people's lives, unfolding and refolding the coordinates of human existence. "With insightful references to cases around the world, this book advances a brilliant holistic theory that offers credibility and significance to the ways revolutions unfold in culturally specific practices without diminishing their political impact and universal aspirations." Behrooz Ghamari-Tabrizi, author of Foucault in Iran: Islamic Revolution after the Enlightenment "This fascinating volume opens up new horizons in the study of revolutionary practice. It is difficult to imagine a more important or original work." David Nugent, author of The Encrypted State: Delusion and Displacement in the Peruvian Andes "This book is a truly original (in all senses of the term) contribution to understanding the global and human condition of far-reaching political, social, and cosmological change." Bjørn Enge Bertelsen, author of Violent Becomings: State Formation, Sociality, and Power in Mozambique"